2011
DOI: 10.1007/s12291-011-0142-2
|View full text |Cite
|
Sign up to set email alerts
|

Production and Purification of Rabbit’s Polyclonal Antibody Against Factor VIII

Abstract: The attempt is made to produce recombinant factor VIII but the first step in producing such product is production and purification of rabbit's polyclonal antibody against factor VIII. The second and third steps involve monoclonal antibody and recombinant factor VIII production. Factor VIII is one of the most important coagulating factor where its deficiency leads to diseases like hemophilia type A or classic. It is an inherited disease. Previously, it was obtained through fractionation of blood plasma of blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Development and uses of polyclonal antibodies in rabbits and hens have been widely described before with inherent variations depending on the nature of the antigen and the dose and route of administration [ 42 , 43 ]. Although only two animals (a pair of hens or rabbits) were used to produce antibodies against each antigen, the immune response of each animal was similar as demonstrated by Western blot analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Development and uses of polyclonal antibodies in rabbits and hens have been widely described before with inherent variations depending on the nature of the antigen and the dose and route of administration [ 42 , 43 ]. Although only two animals (a pair of hens or rabbits) were used to produce antibodies against each antigen, the immune response of each animal was similar as demonstrated by Western blot analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, several research groups described the procedure of anti-FVIII-antibodies generation. For example, Sohrabi et al (2011) used Al(OH) 3 as an adjuvant for rabbit immunization with FVIII. The authors shot 4000 µg of FVIII per each injection and obtained antibody titers between 1/1000 and 1/10,000, lower than the levels obtained with the use of much smaller amounts of antigen immobilized in gel, as described above.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, ammonium sulfate and caprylic acid precipitation, hydroxylapatitechromatography, DEAE ion exchange chromatography and immunoaffinity chromatography, to name a few. The produced antibody is dependent on employing techniques like Western blotting and ELISA [10][11][12]. Recombinant human EPO hormone that has been started to be marketed and used in medical care is purified by several methods that require antibody.…”
Section: Discussionmentioning
confidence: 99%
“…Their results have shown that all of these techniques can purify antigen-specific antibodies of rabbit sera. Sohrabi and colleagues have also used different techniques such as ionexchange, affinity chromatography, ammonium sulfate precipitation of IgG or caprylic acid methods to purify rabbit's polyclonal antibody against recombinant coagulating factor VIII [12,13]. In this research, after polyclonal antibody production in rabbit and purification by various methods, Western blot and ELISA tests were performed to confirm the presence and the levels anti-EPO antibody.…”
Section: Introductionmentioning
confidence: 99%